2012
DOI: 10.1002/syn.21561
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal immune challenge in rats: Altered responses to dopaminergic and glutamatergic agents, prepulse inhibition of acoustic startle, and reduced route‐based learning as a function of maternal body weight gain after prenatal exposure to poly IC

Abstract: Prenatal maternal immune activation has been used to test the neurodevelopmental hypothesis of schizophrenia. Most of the data are in mouse models; far less is available for rats. We previously showed that maternal weight change in response to the immune activator polyinosinic-polycytidylic (Poly IC) in rats differentially affects offspring. Therefore, we treated gravid Harlan Sprague-Dawley rats i.p. on embryonic day 14 with 8 mg/kg of Poly IC or Saline. The Poly IC group was divided into those that lost or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 73 publications
(131 reference statements)
4
48
0
Order By: Relevance
“…GD 14) (Vorhees et al 2012). It should be noted here that male specific effects of poly-I:C on PPI occurred when offspring were exposed at GD9, while femalespecific PPI deficits were found when exposed to poly-I:C at GD14 -therefore the timing of infection may impact the male and female developing brain differently.…”
Section: Prenatal Immune Challenged Modelmentioning
confidence: 71%
See 1 more Smart Citation
“…GD 14) (Vorhees et al 2012). It should be noted here that male specific effects of poly-I:C on PPI occurred when offspring were exposed at GD9, while femalespecific PPI deficits were found when exposed to poly-I:C at GD14 -therefore the timing of infection may impact the male and female developing brain differently.…”
Section: Prenatal Immune Challenged Modelmentioning
confidence: 71%
“…It should be noted here that male specific effects of poly-I:C on PPI occurred when offspring were exposed at GD9, while femalespecific PPI deficits were found when exposed to poly-I:C at GD14 -therefore the timing of infection may impact the male and female developing brain differently. Vorhees et al also found male specific deficits in fear-potentiated memory (cue conditioned freezing) in the offspring of poly-I:C exposed rats, but only following a repeated dosing regimen of poly-I:C injections from gestational day 14-18, while a single injection at day 14 had no such effect on the offspring (Vorhees et al 2012;Vorhees et al 2015). However, spatial memory, as assessed using a spontaneous alternation paradigm in the Y-maze, was specifically disrupted in female mouse offspring exposed to poly-I:C (5mk/kg i.p., GD9, n=5-8/group) (O'Leary et al 2014).…”
Section: Prenatal Immune Challenged Modelmentioning
confidence: 97%
“…However, high etiological validity can come at a cost. When measuring cognition, testing may be confounded by differences in learning (Vorhees et al 2012;Vorhees et al 2015). In addition, these models often produce a variety of nonspecific and diverse neurological changes, thus preventing the study of isolated systems (Hadar et al 2015).…”
Section: Validity Of the Acute Mk-801 Modelmentioning
confidence: 99%
“…[37][38][39][40] Experimental animal models of maternal immune activation have provided insights into these multifactor relationships. For example, mice exposed to immune activation in utero show schizophrenia syndrome-relevant behavioral abnormalities in adulthood, such as impaired sensorimotor gating [41][42][43] and cognitive ability, 41,[43][44][45][46][47] including working memory. 48,49 Maternal immune activation models also show molecular changes that are identified in the PFC of individuals with schizophrenia, 50 including lower expression of PV, 43 GAD67, 51 and GAD67 in PV axonal boutons.…”
Section: Maternal Infection-associated Risk Factors and Pv Basket Celmentioning
confidence: 99%